Impaired Cross-Talk between Mesolimbic Food Reward Processing and Metabolic Signaling Predicts Body Mass Index - Simon, Joe J.; Skunde, Mandy; Hamze Sinno, Maria; Brockmeyer, Timo; Herpertz, Sabine C.; Bendszus, Martin; Herzog, Wolfgang; Friederich, Hans-Christoph (Frontiers in Behavioral Neuroscience, 2014)
The anticipation of the pleasure derived from food intake drives the motivation to eat, and hence facilitate overconsumption of food which ultimately results in obesity. Brain imaging studies provide evidence that mesolimbic brain regions underlie both general as well as food related anticipatory reward processing. In light of this knowledge, the present study examined the neural responsiveness of the ventral striatum in participants with a broad BMI spectrum. The study differentiated between general (i.e. monetary) and food related anticipatory reward processing. We recruited a sample of volunteers with greatly varying body weights, ranging from a low BMI (below 20 kg/m²) over a normal (20 to 25 kg/m²) and overweight (25 to 30 kg/m²) BMI, to class I (30 to 35 kg/m² ) and class II (35 to 40 kg/m²) obesity. A total of 24 participants underwent functional magnetic resonance imaging whilst performing both a food and monetary incentive delay task, which allows to measure neural activation during the anticipation of rewards. After the presentation of a cue indicating the amount of food or money to be won, participants had to react correctly in order to earn “snack points” or “money coins” which could then be exchanged for real food or money, respectively, at the end of the experiment. During the anticipation of both types of rewards, participants displayed activity in the ventral striatum, a region that plays a pivotal role in the anticipation of rewards. Additionally, we observed that specifically anticipatory food reward processing predicted the individual BMI (current and maximum lifetime). This relation was found to be mediated by impaired hormonal satiety signaling, i.e. increased leptin levels and insulin resistance. These findings suggest that heightened food reward motivation contributes to obesity through impaired metabolic signaling.